Identifying additional risk factors for early asymptomatic neonatal hypoglycemia in term and late preterm babies - Yu-Shao Chen; Chung-Han Ho; Shio-Jean Lin; Wen-Hui Tsai (Pediatrics and Neonatology)
Background: Neonatal hypoglycemia is a common metabolic disorder in newborns, which may present with non-specific symptoms or even be asymptomatic. Current guidelines recommend screening for hypoglycemia in at-risk babies (late preterm, small for gestational age, large for gestational age, and infants of diabetic mothers). Past studies have suggested other potential risk factors, such as maternal obesity, gestational hypertension, cesarean section, etc. In this study, we aim to identify additional prenatal and perinatal maternal/fetal characteristics associated with early asymptomatic hypoglycemia in term and late preterm babies. Methods: We performed a retrospective review on medical charts of all newborns, born between January, 2017 and December, 2020, in the well-baby newborn nursery of a tertiary medical center. We identified newborns who had received blood glucose concentration monitor after birth. Detailed prenatal and perinatal maternal/newborn information were collected for analysis. Results: In the study period, 841 newborns had received blood glucose screening after birth. After matching by sex and indication for postnatal blood glucose screen (SGA, LGA, and GDM), 148 newborns were included in the “hypoglycemia group” and 296 newborns were included in the “euglycemia group”. In the univariate analysis, parity, insulin treatment for gestational diabetes mellitus (GDM), and cesarean section were associated with an increased risk for neonatal hypoglycemia. Factors associated with decreased risk included higher gestational age, longer duration of skin-to-skin contact, neonatal hyperthermia, higher maternal labor pain score, and epidural anesthesia administration. By multivariable analysis, insulin treatment for GDM was identified as an independent factor associated with increased risk for neonatal hypoglycemia. Conclusion: Our study showed insulin treatment for GDM to be independently associated with neonatal hypoglycemia. Other risk factors noted in the univariate analysis, such as decreased skin-to-skin contact duration, hypothermia, Cesarean section, and preterm delivery, would require further investigation to confirm the findings.